Notary Authority to Make Certificate of Heir Based On Notary Positions - Miranti Kusuma Wardhani (Sultan Agung Notary Law Review, 2021)
Before the Act No. 30 Of 2004 about notary Occupation being progress, there is no special regulation that is becoming the basic for Notary authority to make the Bank statement for heir in practically in Indonesia. After the Act No. 30 Of 2004 about notary Occupation being progress, the notary authority to make the bank statement for heir is not arranged expressly in section 15 sentence (2). In consequence require by an analysis to notary authority in making Bank statement for heir especially after the Act No. 30 Of 2004 about notary Occupation being progress. This research uses the empirical approach juridically. The example is taken by non random purpose sampling. Analyze done by descriptive, to analyze the notary authority in making bank statement for heir after the Act No. 30 Of 2004 about notary Occupation being progress. Target of this research is to know and studying of arrangement of notary authority in making Bank statement for heir in pursuant to number Act No. 30 of 2004 about notary Occupation, the strength of verification of Bank Statement for Her which made by some different notary people to heir in someone to heir and third party and also sanction to notary and notary responsibility if wronging in Bank Statement for Heir. From research result known that base of Notary authority make the bank Statement for Heir customary law since away back caused a notary assumed by as of side knowing about hereditary law, verification Bank Statement depend on wisdom of justice and sanctions and also notary responsibility if wronging in making Bank Statement Heir that is Section 1365 of the Civil Code. Suggested that a notary authority in making Bank Statement Heir formally cover the authority of functional and heir criterion able to make the Bank statement heir before notary.